2021
DOI: 10.2147/cmar.s282529
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Hub Genes Associated with the Prognosis of Ovarian Cancer Patients via Integrated Bioinformatics Analysis and Experimental Validation

Abstract: Background This study aimed to identify the hub genes associated with prognosis of patients with ovarian cancer by using integrated bioinformatics analysis and experimental validation. Methods Four microarray datasets (GSE12470, GSE14407, GSE18521 and GSE46169) were analyzed by the GEO2R tool to screen common differentially expressed genes (DEGs). Gene Ontology, the Kyoto Encyclopedia of Genes and Genomes, the (KEGG) pathway and Reactome pathway enrichment analysis, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 60 publications
2
1
0
Order By: Relevance
“…In clear cell renal cell carcinoma, inhibiting KIF11 increases the expression level of E-cadherin mRNA and decreases the mRNA level of mesenchymal markers, including N-cadherin and vimentin [118]. Similar results have been observed in ovarian cancer with an increasing level of ZEB-1, a transcriptional repressor of E-cadherin expression, instead of upregulated vimentin expression [134]. Apart from the E-cadherin/N-cadherin phenotypic switch, KIF11 can also regulate the expression of extrinsic factors to play roles in cell migration.…”
Section: Kif11 In Epithelial-mesenchymal Transition (Emt)supporting
confidence: 72%
“…In clear cell renal cell carcinoma, inhibiting KIF11 increases the expression level of E-cadherin mRNA and decreases the mRNA level of mesenchymal markers, including N-cadherin and vimentin [118]. Similar results have been observed in ovarian cancer with an increasing level of ZEB-1, a transcriptional repressor of E-cadherin expression, instead of upregulated vimentin expression [134]. Apart from the E-cadherin/N-cadherin phenotypic switch, KIF11 can also regulate the expression of extrinsic factors to play roles in cell migration.…”
Section: Kif11 In Epithelial-mesenchymal Transition (Emt)supporting
confidence: 72%
“…The bioinformatic obtained results have been validated by an in vitro ovarian cancer model, represented by SKOV3 cell line: silencing of KIF11 results in a significant reduction of cell proliferation probably due to induction of apoptosis, as demonstrated by the increased activation of Caspase 3/7. Furthermore, as previously reported for other tumor models, KIF11 knockdown determines the effect not only on mitotic activity, but also on nonmitotic activity: siKIF11 reduced the invasion of SKOV3 cells and modified the expression levels of epithelial to mesenchymal transition genes, such as an upregulation of E-cadherin mRNA expression and a downregulation of N-cadherin and vimentin mRNA levels [ 54 ]. The bioinformatic results were also confirmed by Dong et al [ 53 ], suggesting that further investigation is required to better clarify Eg5 role in this malignancy.…”
Section: Eg5 In Tumor Onset and Progressionsupporting
confidence: 53%
“…A lot of studies also suggest that involvement of carcinogenesis in various cancers (lung, liver, and breast cancer) is due to highly expressed TOP2A thereby causing slow prognosis in patients [ 31 33 ]. TOP2A also promotes tumorigenesis in ovarian cancer which regulates the TGF- β /Smad pathway; the expression of TOP2A was also found to correlate with poor survival of ovarian cancer patients and platinum resistance [ 34 , 35 ]. Our results have shown that upregulation of TOP2A in tissues of ovarian cancer is linked with poor prognosis.…”
Section: Discussionmentioning
confidence: 99%